Pyoderma Gangrenosum: A Nightmare for Breast Surgery-Two Case Reports - Gülşen Akoğlu; Murat Demiriz; Kerim Bora Yılmaz (European Journal of Breast Health)
Pyoderma gangrenosum (PG) is a rare, chronic, neutrophilic dermatosis characterized by painful ulcers that are often misdiagnosed as wound infections. We report two cases of postsurgical PG following breast surgery: A 46-year-old woman with a non-healing ulcer after a breast biopsy and a 37-year-old woman with wound dehiscence after bilateral reduction mammoplasty. Both cases were initially managed with repeated debridements, antibiotics, and wound care without improvement. The diagnosis of PG was made based on the increase in wound size and irregularity. Treatment with oral doxycycline and topical tacrolimus led to favorable healing within four months. Breast surgical tehniques, which aim to achieve aesthetic results using intraglandular flaps, have become an important part of clinical practice in breast surgery. Early diagnosis and appropriate management are crucial in postsurgical PG to avoid misdiagnosis and ineffective treatments that cause patient disfigurement.